Building materials with historical and heritage interest – A database in progress - Santos Silva, A. (2018)
Conservation and restoration of architectural heritage requires knowledge of the conservation state of its constituent materials in order to provide recommendations concerning the intervention plan, and the materials and the techniques to be used. Information on physical, chemical and mechanical characterization of materials, when available, is usually shared by different actors, but is not normally accessible by the general public. In this context, the DB-HERITAGE project intends to build a reference sample collection or repository for historical materials and an IT-tool to collect the related data on construction materials history, properties, and performance. This database is being developed to categorize materials by type and function, addressing the relevant issues in the historical context of construction materials. An overview of the database tools will be presented in this paper, exemplifying some of its outputs.